Thermally induced fixed diradical generation on solid supports for surface‐initiated polymerization - Gure, Baris; Bicak, Niyazi (Wiley, 2012)
AbstractA method is presented for generation of all surface‐bound radicals on solid polymer surfaces. Thus, secondary amide group of newly synthesized crosslinking comonomer, methacryloyloxyethyl methacrylamide was determined as versatile precursor for generation fixed diradicals on solid microspheres, obtained by copolymerization with methyl methacrylate (MMA) in aqueous suspension. Nitrosoation of the secondary amide groups on the microbeads and followed thermolysis above 90 °C was demonstrated to give surface‐bound radicals, capable of initiating polymerization of vinyl monomers, such as; styrene, MMA, N‐vinyl formamide, and N‐vinyl, 2‐pyrrolidone, as evidenced by H NMR, Fourier transform infrared, thermogravimetric analysis, and differential scanning calorimeter techniques. Appreciable grafting yields (55.1%–286.1%) and low free‐homopolymer formation (7.2%–19.7%) were noted within 6 h of the grafting at 100 °C in each case. This strategy involving the use of amide functional crosslinker seemed to be generally applicable to generate surface‐bound radicals for surface‐initiated polymerization from various solid substrates. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2012